Camera traps to study the forest elephant's (Loxodonta cyclotis) response to chilli pepper repellent devices in Gamba, Gabon - Steeve Ngama; Lisa Korte; Mireille Johnson; Cédric Vermeulen; Jérôme Bindelle (Nature Conservation Research: Заповедная наука, 2018)
In Central Africa, Gabon is a forested country with a rich biodiversity where conflict between wild animals and humans is common and causes innumerable damage to crops. The worst crop raiders are elephants, which can destroy an entire crop in a single night. These raids threaten people's livelihoods as well as elephants because angry farmers often retaliate with killing campaigns against crop raiding elephants. To keep elephants out of farms the use of chilli pepper is recommended as a non-lethal method. But only a few studies have tested methods to use chilli pepper to deter elephants in Gabon. Results from this study give a starting point for understanding how forest elephants react to devices using chilli pepper as a deterrent based on sequential camera trap photos. A chilli pepper device that resulted in splashing concentrate on the elephant face proved to be the most effective at deterring elephants. Surprisingly, chilli pepper concentrate directly applied to mango fruits did not deter elephants from eating the fruits, although it probably caused some discomfort. To make effective deterrent devices with chilli pepper future works need to focus on exploring practices to reach the elephant face with the least, safe quantity of chilli pepper and which will have enough strong deterrent effect.